2014
DOI: 10.2174/1573399810666140425160811
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and Memory: Using Neuroimaging to Understand the Mechanisms

Abstract: Abstract:The most robust and frequently reported cognitive deficits in type 2 diabetes (DM2) are those that relate to memory. Behavioural research has identified a number of potential contributory physiological factors, including abnormalities in glucose metabolism, such as hyperglycaemia and hypoglycaemia. The impact of these mechanisms on memory has been further investigated through the use of both structural and functional neuroimaging. Structural brain imaging has indicated that memory impairments in DM2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…In this regard, previous work has mainly investigated T2D related decline in single item memory, for example, word list learning (Jones et al, 2014;Stewart & Liolitsa, 1999), which is a different process with distinct neural substrates as compared to associative memory (Ranganath, 2010;Wang, Li, Li, & Zhang, 2013). As associative memory, compared to single item memory, is more affected in Alzheimer's disease (Blackwell et al, 2004;Fowler, Saling, Conway, Semple, & Louis, 2002;O'Connell et al, 2004;Parra et al, 2009;Swainson et al, 2001) and T2D patients exhibit an increased risk in developing Alzheimer disease (Kuusisto et al, 1997;Leibson et al, 1997;Ott et al, 1999), our study of associative episodic memory in T2D provides a relevant contribution to the understanding of cognitive decline in T2D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, previous work has mainly investigated T2D related decline in single item memory, for example, word list learning (Jones et al, 2014;Stewart & Liolitsa, 1999), which is a different process with distinct neural substrates as compared to associative memory (Ranganath, 2010;Wang, Li, Li, & Zhang, 2013). As associative memory, compared to single item memory, is more affected in Alzheimer's disease (Blackwell et al, 2004;Fowler, Saling, Conway, Semple, & Louis, 2002;O'Connell et al, 2004;Parra et al, 2009;Swainson et al, 2001) and T2D patients exhibit an increased risk in developing Alzheimer disease (Kuusisto et al, 1997;Leibson et al, 1997;Ott et al, 1999), our study of associative episodic memory in T2D provides a relevant contribution to the understanding of cognitive decline in T2D.…”
Section: Discussionmentioning
confidence: 99%
“…, psychomotor speed (Gregg et al, 2000;Reaven et al, 1990), processing speed (Messier, 2005), verbal fluency (Kanaya, Barrett-Connor, Gildengorin, & Yaffe, 2004;Reaven et al, 1990), executive function (Munshi et al, 2006;Perlmuter et al, 1984;Reaven et al, 1990), attention (Fontbonne, Berr, Ducimetiere, & Alperovitch, 2001), and several domains of memory (Grodstein, Chen, Wilson, & Manson, 2001;Messier, 2005;Mooradian, Perryman, Fitten, Kavonian, & Morley, 1988;Munshi et al, 2006;Perlmuter et al, 1984). Among these impairments, the most robust and frequently reported cognitive deficits in T2D are episodic memory dysfunction (Jones, Riby, Mitchell, & Smith, 2014). Not surprisingly, T2D associates with a greater prevalence of neurocognitive disorders and Alzheimer's disease in particular (Biessels, van der Heide, Kamal, Bleys, & Gispen, 2002;Leibson et al, 1997;Ott et al, 1996Ott et al, , 1999.…”
mentioning
confidence: 99%
“…The hippocampus is a brain region important for learning, and memory formation and consolidation. Some preliminary data suggest that atrophy in the hippocampal area may be primarily responsible for memory impairment reported in this population (Jones, Riby, Mitchell, & Smith, 2014). Using the diffusion magnetic resonance imaging technique, Reijmer, Brundel, et al (2013) found microstructural white matter abnormalities and disruptions in the white matter network in persons with T2DM compared with age-, sex-, and education-matched controls.…”
Section: Resultsmentioning
confidence: 98%
“…Functional imaging data further suggests diminished connectivity between the hippocampus and the frontal and temporal regions (23). Thus, atrophy in the hippocampal area and altered neuronal connectivity might be responsible for the memory impairment in subjects with T2D (23).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is some evidence that higher blood glucose levels, even in the normal range, are associated with atrophy in the hippocampus and amygdala, brain regions critically important for memory (22). Functional imaging data further suggests diminished connectivity between the hippocampus and the frontal and temporal regions (23). Thus, atrophy in the hippocampal area and altered neuronal connectivity might be responsible for the memory impairment in subjects with T2D (23).…”
Section: Discussionmentioning
confidence: 99%